Trainer Smart Building Sebagai Media Pembelajaran Teknik Instalasi Tenaga Listrik - Pratama, Wahyu Alisia; Fatkhurrokhman, Mohammad; Irwanto, Irwanto (Jurnal Pendidikan Teknik Elektro, 2025)
This research aims to (1) Create Smart Building learning media at Sekolah Menengah Kejuruan Negeri (SMKN 1 Kramatwatu Department of Electrical Power Installation Engineering on the subject of Electrical Lighting Installation; (2) Determine the feasibility level of learning media and jobsheets of Smart Building trainers in the Electrical Lighting Installation course at SMKN 1 Kramatwatu majoring in Electrical Power Installation Engineering. This research is a type of research and development regarding the 4D model. The data collection method in this study is by collecting interview data and questionnaires. The data analysis technique uses media feasibility analysis. Based on the results of the research that has been carried out, trainer learning media and smart building jobsheets have been successfully developed. The learning media is said to be "Very Feasible" to be used at SMKN 1 Kramatwatu based on the media feasibility test, material feasibility test and user response test that has been carried out.